Village Owned Enterprises as a Financial Support Mechanism for Educational Management and Village Development - Sulhan S. Marzuki; Siti Aminah Hamzah Karim; Rosida P. Adam; Abdul Aziz R. (Al-Qalam Institue, 2026)
This study aims to analyze the role of Village-Owned Enterprises (BUMDes) in enhancing Village Original Revenue (PADes) through the application of good governance principles, namely cooperativeness, emancipatory values, participation, transparency, and accountability. The research employed a qualitative descriptive approach to capture an in-depth understanding of governance practices and their implications for village economic performance. Data were collected through in-depth interviews, direct observation, and document analysis involving village government officials, BUMDes managers, and community members. The results indicate that BUMDes contributes significantly to increasing village revenue through the management of rental-based business units, such as equipment and service facilities, which are responsive to community needs. The implementation of cooperative principles is reflected in strong collaboration among stakeholders, while emancipatory practices ensure equal access and non-discriminatory services for all community members. Participatory governance is evident in community involvement throughout the planning, implementation, and evaluation processes. Transparency and accountability are demonstrated through open financial reporting and periodic performance accountability reports. Beyond financial contributions, BUMDes also generates broader socio-economic impacts, including community empowerment, employment opportunities, and the stimulation of local economic activities. These findings imply that strengthening governance-oriented management within Village-Owned Enterprises is crucial for ensuring sustainable village development and maximizing the contribution of local economic institutions to village financial independence.